Sources of Resistance to Stem Rust (Puccinia graminis f. sp. tritici) in Improved Durum Wheat (Triticum turgidum l.) Varieties of Ethiopia - Mekonnen, Mequanint Andualem; Admasu, Merkuz Abera; Hei, Netsanet Bacha (Current Research in Agricultural Sciences, 2019)
Stem rust disease caused by Puccinia graminis f. sp. tritici (Eriks and E. Henn) possess the greatest threat to global wheat production due to continuously producing new races that can attack previously resistant varieties. This investigation was therefore conducted under greenhouse and field conditions by evaluating durum wheat (Triticum turgidum L.) cultivars along with a susceptible check for their resistance to stem rust during the 2017 main cropping season. Greenhouse evaluation was conducted at Ambo for race TTTTF. The field experiment was undertaken at Adet and Debre-Tabor in a randomized complete block design (RCBD) with three replications. The spreader row Morocco was inoculated with a virulent race (TTTTF) at stem elongation. Field resistance at the adult plant stage was assessed through final disease severity (FRS), coefficient of infection (CI), and area under disease progressive curve (AUDPC). Durum wheat cultivars Mettaya and Oda were found to be resistant both at the seedling and post seedling stages suggesting resistance confer by a major gene. Whereas Bakalcha, Lelisso, Ilani and Yerer showed low disease severities ˂30 with lower AUDPC values (˂500) and CI (˂20) and were identified to have a good level of field resistance for stem rust population present at Adet and Debre-Tabor. High correlation coefficients were observed between stem rust resistance parameters. Among the cultivars having a good level of resistance Lelisso, Bichena and Bakalcha produce high yields with heavy kernel weight in both locations. The resistance cultivars identified from the present study can be used for further wheat improvement programs.